Options to achieve net-zero emissions from agriculture and land use changes in Latin America and the Caribbean - Patrice Dumas; Stefan Wirsenius; Tim Searchinger; Nadine Andrieu; Adrien Vogt-Schilb (Inter-American Development Bank (IDB), 2022)
Eleven countries in Latin America and the Caribbean have pledged to reach net-zero emissions by around 2050. Changes in the food system are key to reach these carbon neutrality goals, as agriculture and resulting land-use changes are responsible for almost half of greenhouse gas emissions in the region. We quantify the effect of supply-side (e.g., yield improvements, silvopasture, agroforestry) and demand-side (e.g., reduction of waste and losses, changing diets) options to reduce emissions and transform the land use system in a net carbon sink by 2050 while improving nutrition for the growing population. We consider both direct agriculture emissions and the pressure that food production puts on land use changes, and track separately emissions that happen in the region and emissions linked to trade. Our findings confirm that cattle plays a preponderant role, emitting nearly 60% of greenhouse gas emissions from agriculture and land-use change. Reaching a net-negative emissions food system able to balance emissions from the rest of the economy will require ambitious and sustained improvements in yields and changes in diets to moderate the increasing demand for beef, continuously decrease the share of land dedicated to agriculture, and increase instead land dedicated to carbon sequestration and biodiversity preservation.
Keywords: Q54; Q15; Q17; Q18; 330; Agriculture; Forestry and Other Land Use; AFOLU; food; yields; diets; decarbonization; carbon neutrality